Bladder and bowel continence in bilateral cerebral palsy: A population study. Issue 6 (December 2016) - Wright, A.J.; Fletcher, O.; Scrutton, D.; Baird, G.
Summary: Introduction: The attainment of continence is an important milestone in all children, including those with disability. Objective: To describe the age of bladder and bowel continence in children with bilateral cerebral palsy (BCP), and the association with intellectual impairment (II) and severity of motor disability. Patients and methods: The parents of 346 children with BCP were interviewed as part of a population-based prospective study of the children at 3, 7, and 17 years of age. The age of bladder and bowel continence by day and night was ascertained and compared with controls from the Avon Longitudinal Study of Parents and Children (ALSPAC). Results: The median age for daytime bladder and bowel continence in BCP children was 5.4 years compared with 2.4 years in the controls. At 13.8 years of age, 59.4% of BCP children and 99% of controls were continent by day. In BCP children, there was no difference between the attainment of daytime bladder and bowel control. Night-time bladder and bowel control was slower and less completely attained, with 50% of BCP children continent by the age of 11.8 years compared with 3 years in control children. At 13.8 years of age, 51.9% of BCP children compared with 99.4% of controls were continent for bowel and bladder at night. Gross Motor Functional Classification Score (GMFCS) and intellectual ability (IA) (II) were strongly associated with continence attainment ( P < 0.0001), but gender was not. Discussion: Delayed and less complete continence attainment was noted in other clinic series of children with cerebral palsy (including hemiplegics) and children with II. Severity of motor disability (GMFCS), and II impacted on other aspects of toilet training, such as: motivation, understanding, communication, and independence skills. The presence of neurogenic bladder and bowel dysfunction can occur in all levels of GMFCS. Thus, there are many reasons that can prevent continence attainment. Conclusions: Children with BCP achieved day and night-time bladder and bowel continence more slowly and less completely than controls, with 60.8% being continent by day and 54.6% by night at the age of 17 years. The majority of BCP children who were continent by day had achieved this by the age of 5.5 years (86%). At least 88% of BCP children with GMFCS I/II and normal, specific or mild learning impairment were continent for bladder and bowel by day and night. Expectations should be shared with parents, and failure to attain expected continence should be actively investigated.